Astragaloside IV Treats Parkinson’s Disease by Regulating the Proliferation and Differentiation of NSCs through the SHH–Nurr1 Pathway - Zicong Wu; Jianing Zhang; Han Gao; Wentao Li (Stem Cells International)
Recently, there has been a surge of interest in enhancing the differentiation of neural stem cells (NSCs) and supplementing dopamine neurons as a potential treatment for Parkinson’s disease, the second most prevalent neurodegenerative disorder. Two factors, sonic hedgehog (SHH) and nuclear receptor–related 1 protein (Nurr1), have been identified as influential in NSCs differentiation. Additionally, Astragaloside IV (AS-IV), an active compound derived from Astragalus, has also been discovered to impact NSCs differentiation. To assess the effects of AS-IV on cell activity, CCK-8 and flow cytometry techniques were employed. Meanwhile, western blotting, immunofluorescence, and real-time PCR were utilized to detect protein expression both in vivo and in vitro. Furthermore, siRNA assay was used to verify the association between SHH and Nurr1 and to investigate whether AS-IV exerts its effects through this pathway. The experimental findings revealed that AS-IV enhances cell activity and promotes the expression of differentiation proteins related to NSCs. Furthermore, the relationship between the SHH–Nurr1 pathway was confirmed, demonstrating that AS-IV induces NSCs differentiation via this pathway. Consequently, SHH, acting as the upstream signaling pathway of Nurr1, influences its expression, while AS-IV regulates the proliferation and differentiation of NSCs by modulating the SHH–Nurr1 pathway.